The effect of various denture cleansers on porosity and discoloration level of acetal resin denture base - Ollive, Gabriella Maria; Dipoyono, Haryo Mustiko; Ismiyati, Titik (Majalah Kedokteran Gigi Indonesia, 2023)
Denture cleansing is one clinical parameter of successful denture wearing. This study aims to examine the effect of the type of denture cleanser on porosity and discoloration of acetal resin as a denture base. Twenty-four samples of acetal resin with 10 mm in diameter and 2 mm in thickness were divided into four groups. Porosity was measured using the wet and dry sample measurement method, and color value levels were measured using chroma meter for all samples. All of the samples were soaked into four types of denture cleanser: distilled water, alkaline peroxide tablets, 0.2% chlorhexidine gluconate, and 0.5% sodium hypochlorite for seven days, then the final porosity and color value level were assessed. The results showed that there were significant differences between groups in porosity and in color change of acetal resin (p < 0.05). Pearson’s correlation test showed that there was a positive correlation between the porosity level and discoloration level of acetal resin (p < 0.05). The research discovered that the type of denture cleaner has a significant influence on the porosity and color change of acetal resin. Sodium hypochlorite has the highest porosity and color change when compared to other cleansing agents.